+0  
 
+15
791
2
avatar+1833 

p is inversely proportional to the square of (q + 4).

p = 2 when q = 2.

 

Find value of p when q = -2.

 Feb 12, 2017
 #1
avatar+111435 
0

p  = k / (q + 4)^2

 

And we know that

 

2  = k / (2 + 4)^2

 

2  = k / (6)^2

 

2 = k / 36

 

2(36)  = k  = 72  = the proportionality constant

 

So

 

p = 72 / ( -2 + 4)^2

 

p = 72 / (2)^2

 

p  = 72 / 4

 

p = 18     when q  = -2

 

 

 

cool cool cool

 Feb 12, 2017
 #2
avatar-26 
0

is it thelegend27?

 Feb 12, 2017

16 Online Users

avatar